Potential Assessment Model of Planning, Procurement and Construction Management In Reducing Cost Inefficiency Due To Building Construction Material Waste (Case Study of SOE Contractors In Makassar City) - Rusdi Latief (Lowland Technology International, 2020)
The emergence of material wastes during the buildingconstruction is inevitable, with direct and indirect impact costs.However, this can be minimized by applying the concept ofproper management on the planning, procurement andconstruction stages. This study, therefore, aims to analyze thelevel of potential influence on the application of managementconcept to the building construction materials. The dynamicsimulation test was used to reduce the ineffective impact ofmaterial cost, reviewed by the parties involved in the project.Data were obtained by distributing questionnaires to buildingcontractors consisting of experienced and responsible workers.Furthermore, the data were analyzed and interpreted using thepath relationship concept, with the dynamic technique used todetermine the potential value of the model against timechanges. The results obtained in the Time Series Analysis arethe dynamic test of the model concept. The results of thedynamic test analysis on the model concept is simultaneouslyintegrated to the planning, procurement and constructionstages, to reduce the impact of cost inefficiency in buildingconstruction. The result also showed that there is a future74.41% decrease in the average construction waste by a stateowned contractor with the ability to optimally reduce costinefficiencies.